How Do Price Perceptions of Different Brand Types Affect Shopping Value and Store Loyalty?. Issue 12 (December 2015) - Diallo, Mbaye Fall; Coutelle‐Brillet, Patricia; Rivière, Arnaud; Zielke, Stephan
ABSTRACT: This research investigates the relationships among price perceptions for different brand types (national brands, standard store brands, regional store brands, organic store brands), shopping value dimensions (quality, price, social, and emotion value), and store loyalty (retention and word of mouth (WOM)). A comprehensive model depicts determinants of customer store loyalty. Using structural equation modeling, the model test includes 671 consumers intercepted during shopping trips. The data analysis yields several surprising results. In particular, low product price perceptions do not necessarily signal negative store quality evaluations. Shopping value dimensions influence store retention loyalty and WOM behavior differently. Furthermore, different brand types exert distinct effects on the value creation process. Favorable prices for national and standard store brands have comparable positive effects on store price value and emotional value creation; appealing prices of regional store brands instead reduce the emotional value of the store, and low prices for organic store brand products significantly increase social value creation.